The Effect of Gross Domestic Product (GDP) on Foreign Debt with Corruption Perception Index as a Moderating Variable - Reza Pramudya Hermawan Putra (Riwayat: Educational Journal of History and Humanities, 2023)
The study aims to analyze the correlation between Gross Domestic Product (GDP) and the amount of foreign currency-denominated national debt, incorporating the Corruption Perception Index as a moderating variable. The study seeks to provide an in-depth understanding of the relationship between GDP and foreign debt, considering the potential moderating effect of corruption perception.The studyused a quantitative approach, employing secondary data on GDP, foreign debt, and corruption perception index. The data will be collected from reliable sources such as national statistical agencies and international organizations. Multiple regression analysis will be conducted to examine the relationship between GDP and foreign debt, while also considering the moderating effect of corruption perception . The results contribute to the existing literature on the relationship between GDP and foreign debt, particularly in the context of corruption perception. The study provides insights into the potential impact of corruption on the relationship between GDP and foreign debt, highlighting the importance of addressing corruption in managing national debt. The results can inform policy makers and stakeholders in formulating strategies to promote economic growth, manage foreign debt, and combat corruption .